Infectiousness of Ixodes Persulcatus Ticks with Pathogens of Various Diseases in Endemic Regions of European Russia - O.N. Lyubeznova; A.L Bondarenko; L.S. Karan (Aktualʹnaâ Infektologiâ, 2014)
Objective: to study the infectiousness of ticks (Ixodes persulcatus) with pathogens of various diseases in the Kirov region. Materials and Methods. We investigated 322 ticks collected in the southern taiga subzone, for the presence of DNA/RNA of tick-borne encephalitis virus, Borrelia burgdorferi sensu lato, Borrelia miyamotoi, Anaplasma phagocytophilum, Ehrlichia muris/Ehrlichia chaffeensis. Results. 48.1 % of the investigated ticks were infected with pathogens of any transmissible diseases. Borrelia burgdorferi s.l. were detected in 45.3 % of the ticks, B.miyamotoi — in 3.1 %, E.muris — in 12.4 %, tick-borne encephalitis virus — in 1.2 %. Quarter of the ticks (25.8 %) contained pathogens of multiple diseases. Double mixed infection was detected in 36 ticks, triple — in 5. Of the total number of infected ticks (n = 155), males accounted for 56.1 % and females — 43.9 %. Conclusion. Kirov region is an active natural focus of transmissible infections. Quite often tick contains two or three pathogens. It is necessary to continue the monitoring of the natural foci to develop more adequate preventive measures against tick-borne infections.